Strengthen Commitment to Educational Goals Through Targeted Monitoring and Evaluation Activities - Rezeki, Ketiara; Nasution, Saharni; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar, 2023)
The context of this study is the need for consistent sustainable quality across Indonesia. Education must also be able to positively develop the potential of students, so that they have the strength of religious spirit, intelligence, personality, ethics and noble skills that they, society, the nation and the State need. To achieve the education goals, it is important to ensure the implementation of four pillars: a) access to education, i.e. providing convenience and equal opportunities for each to access education. Besides access to education, b) equity means fairness in obtaining equal educational opportunities for different groups in society, c) finance, which means that every citizen has obligation to receive government-funded primary and secondary education, d) monitoring and evaluation, i.e. monitoring of policy and evaluation to improve and perfect its implementation. The goal of this study is to describe the four pillars of education (access, equity, financing, and assessment). The research method uses a literature review and a literary approach. Six articles were reviewed to collect data from the fields of education, access, equity, finance, monitoring and evaluation.The conclusion of the study shows that the success of a country's educational goals lies in the proper implementation of the above four pillars. Equal rights in education are an important aspect of equality and social justice. It is important to ensure that funding is identified in the APBN in accordance with section of each pillar.